The use of ASR-CAI tool and its impact on interpreters’ performance during simultaneous interpretation - Pannapat Tammasrisawat (Chulalongkorn University, 2021)
Ever since automatic speech recognition (ASR) was introduced as a means to improve the terminology lookup mechanism and reduce additional cognitive effort in performing a terminology query, many studies have been conducted to investigate the use of ASR-CAI tools in simultaneous interpretation (SI). However, few studies have implemented the process-oriented method in addition to the product-based method in analyzing how the use of ASR-CAI tools may affect the interpreting process. By using both product/process-oriented approaches, this paper set out to investigate the impact of ASR-CAI tool on interpreters’ overall performance. The results showed that the support of ASR-CAI tool led to a significant reduction in error rate and omissions as well as improved the quality of terminology rendition. The paper also discussed the impact of ASR-CAI tool on interpreters’ processing capacity and cognitive effort during SI. In addition, potential benefits and limitations of ASR-CAI tool were analyzed to provide a better understanding regarding the tool’s usability so that such tools can be better integrated into the interpreting process.